Practising Ecumenism Through Boundary Work and Meta-Coding. Issue 2 (4th March 2018) - Kirsch, Thomas G.
Abstract : Drawing on ethnographic fieldwork on religion in Zambia, this article engages critically with approaches that suggest that ecumenism necessarily occurs across socio-religious boundaries. I argue that the objective of ecumenism – namely, good-willed co-operation between religious practitioners who are otherwise separated from each other in terms of their institutional affiliations – can also be attained through boundary work and use of the meta-codes 'non-Christian – Christian' and 'Christian –"real" Christian'. I contend that using these meta-codes in the logic of what has been called 'fractal recursion' allows people to stress situationally the existence of commonalities between religious practitioners and/or religious groupings that, at other points in time, are perceived to be different from each other. In this way, the shifting of categorical boundaries produces ecumenical reality effects.